Influence of organizational culture factors on employee performance at PT. Bank Syariah Mandiri Malang branch - Mochamad Anwar Rosyidi (Central Research Institute for Agriculture (CeRIA), 2021)
This research is to find out how the influence of organizational culture on employee performance. In the context of empowering human resources, in order to produce professional employees with high integrity, it is necessary to have a company standard reference imposed by something. The standard reference is an organizational culture that systematically guides employees to improve their performance. One of the elements that influence employee behavior is the environment of the employee itself, which in this case is the surrounding corporate culture. Organizational culture can influence the way employees behave, the way they describe their work, the way they work with colleagues, and the way they view the future with broad insights defined by their norms, values, and beliefs. Organizational culture determines what can and cannot be done by members of the organization, determines the normative limits of the behavior of members of the organization, determines the nature and form of organizational control and supervision, determines the managerial style that can be accepted by members of the organization, determines the right way of working, and so on. -other. Thus the data is explained through a description of the frequency and proportion. Data analysis using multiple linear regression analysis techniques, and determination. To test the hypothesis is done by using the f test and t test. This study shows that (1) organizational culture has a simultaneous effect on employee performance. (2) there is a dominant influence between trustworthiness and tabligh culture on employee performance. The dominant variable affecting employee performance is the tabligh variable.